Table of Content - - (Journal of Curriculum and Teaching Methodology, 2023)
Table of Content: 1. Efficiency of proposed teaching program based on (TRIZ) theory in developing critical thinking skills of science course, among female students at Grade six in Riyadh Mrs. Anwar Ayed Al-Anazi, Prof. Hamad Abdullah Al-Qumaizi 2. The role of virtual classrooms in improving the educational process from the point of view of private school teachers for the primary stage in Jeddah Governorate Mrs. Abrar Salem Al-Harbi 3. Developing educational curricula in the Kingdom of Saudi Arabia and its impact on international tests’ results compared to the experiences of England, Finland, and Singapore Mrs. Azizh Abdullah Almatroodi 4. The effectiveness of the electronic applications of mental arithmetic on the development of mathematical power with primary school students Mrs. Khawla Abbas Al Qassim 5. Challenges of Using E-learning in Medical Education Based on Medical Students’ Opinion Mrs. Refaa Hussein Alqahtani